Genetic testing for maturity-onset diabetes of the young resulting in an upgraded genetic classification of an HNF1A gene variant: a case report - Pollack-Schreiber, Naama; Nwosu, Benjamin Udoka; Salemi, Parissa (Frontiers in Endocrinology, 2023)
The frequent misdiagnosis of MODY (Maturity-Onset Diabetes of the Young) subtypes makes it necessary to clarify the clinical spectrum of the disease phenotypes in suspected subjects so that accurate diagnosis and management plans can be introduced very early in the course of the disease. We report the case of a MODY subtype that was initially characterized as variant of uncertain significance (VUS) but was later changed to a likely pathogenic variant following our report of two cases where the full expression of the clinical phenotype was described. HNF1A-MODY (MODY 3) is one of the most common subtypes of Maturity Onset Diabetes of the Young. Due to its variable clinical presentation, and the concerns with being misdiagnosed as either type 1 or type 2 diabetes, DNA sequencing is needed to confirm the diagnosis. This case report illustrates the clinical scenario leading to the identification of the gene variant c.416T>C(p. Leu139Pro) in the HNF1A gene, initially reported as a VUS and later upgraded to a likely pathogenic variant. Though the mutation was described in two Czech family members in 2020, the clinical course and phenotype was not characterized. Therefore, there was the need to fully describe the spectrum of the disease arising from the mutation. The case report fully describes the clinical spectrum of this mutation and provides much needed clinical management approaches to the wider scientific community.